2015
DOI: 10.11648/j.ajaf.20150304.14
|View full text |Cite
|
Sign up to set email alerts
|

Herbaceous Species Diversity in Kanawa Forest Reserve (KFR) in Gombe State, Nigeria

Abstract: Abstract:The study was conducted between 2009 and 2011 in Kanawa Forest Reserve (KFR) in order to determine the impact of anthropogenic pressures and environmental changes of the herbaceous species. The project area was divided into six sites following the variety of land forms in the forest and three transects measuring 100m were laid within each site. Point Centered Quarter (PCQ) sampling method was used. Data obtained were analyzed for relative density, relative frequency, and importance value index. A tota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 17 publications
1
2
0
Order By: Relevance
“…Other types of weed example are Alternanthera spp, Brachiaria falcifera, Brachiaria lata, Eragrostis ciliaris, Echinochloa crusgali, Chloris pilosa, Digitaria horizantalis, Dactyloctenium aegyptinum, Cenchrus biflorus, Pennisetum pediculatum, Pennisetum polystachion, Paspalum scrobiculatm were used as forage/fodder for animals. They provide sources of nutrition; this is consistent with the works of Abba, et al [30] in their study of Herbaceous species diversity in Kanawa forest reserves, Gombe State, Nigeria where they also mentioned the use of Chloris pilosa, Digitaria horizantalis, Eragrostis ciliaris, Pennisetum pediculatum as forage or fodder. It is also consistent with the works of Panda [10] who reported the use of Echinochla crusgali, Alternanthera spp.…”
Section: Discussionsupporting
confidence: 85%
“…Other types of weed example are Alternanthera spp, Brachiaria falcifera, Brachiaria lata, Eragrostis ciliaris, Echinochloa crusgali, Chloris pilosa, Digitaria horizantalis, Dactyloctenium aegyptinum, Cenchrus biflorus, Pennisetum pediculatum, Pennisetum polystachion, Paspalum scrobiculatm were used as forage/fodder for animals. They provide sources of nutrition; this is consistent with the works of Abba, et al [30] in their study of Herbaceous species diversity in Kanawa forest reserves, Gombe State, Nigeria where they also mentioned the use of Chloris pilosa, Digitaria horizantalis, Eragrostis ciliaris, Pennisetum pediculatum as forage or fodder. It is also consistent with the works of Panda [10] who reported the use of Echinochla crusgali, Alternanthera spp.…”
Section: Discussionsupporting
confidence: 85%
“…There were 24 species of grasses of poaceace family found within the study area and Pennisetum polystachion, Sporobulus pyramidalis, Andropogon gayanus and Eleusine indica which are from the subfamily Panicoideae, Sporoboleae, Andropogoneae, and Eragrostideae respectively is more abundant in all the 8 zones of the study area. The result of Shannon Wienner index (2.59) in this study showed that there is high diversity of species of poaceae family in the study area and this is a great potential which is to be utilized for conservative and ecological purposes rather than attendant clearing and destruction of these plants [16]. The high value for the Shannon Weinner Index may also be indicative of the healthy and thriving plant community in the study area [17].…”
Section: Discussionmentioning
confidence: 53%
“…Weeds used as food includes Amaranthus spinosus, Portulaca oleraceae, Cassia obtusifolia, Corchorus aestuans, Corchorus olitorius, Corchorus tridens, Alternanthera sessilis, and Chrysanthemum indicum, even though some community members are not aware of the uses of some weeds as sources of food. Panda et al [83] reported Amaranthus sessilis, spinosus, Portulaca oleracea plants were used as sources of food, other types of weed like Alternanthera spp, Brachiaria falcifera, Brachiaria lata, Eragrostis ciliaris, Echinochloa crusgali, Chloris pilosa, and Digitaria horizantalis, Dactyloctenium aegyptinum, Cenchrus biflorus, Pennisetum pediculatum, Pennisetum polystachion, and Paspalum scrobiculatm were used as forage and fodder for animals [20], weeds as sources of nutrition for animals was also reported by Mohammed et al [88] on their study of Herbaceous species diversity in Kanawa forest reserves, Gombe State, Nigeria Chloris pilosa, Digitaria horizantalis, Eragrostis ciliaris, and Pennisetum pediculatum as forage or fodder for animals. Panda et al [83] also reported the use of crusgali, Alternanthera spp.…”
Section: Discussionmentioning
confidence: 99%